GROUND UP CITIZENSHIP: ROOTED CHILDREN (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Ground up citizenship: Rooted Children.This paper explores how rights and protections, even citizenship, could be constructed around the vulnerable child, rather than being derived solely from state or nation. It provides examples of emerging ‘alternative communities’ doing just this and asks what role the church could have in reimagining and modelling communities that transcend borders, proclaim the gospel, and redefine family and mission.